Genomic and Immunogenic Protein Diversity of Erysipelothrix rhusiopathiae Isolated From Pigs in Great Britain: Implications for Vaccine Protection - Forde, Taya L.; Kollanandi Ratheesh, Nichith; Harvey, William T.; Thomson, Jill R.; Williamson, Susanna; Biek, Roman; Opriessnig, Tanja (Frontiers in Microbiology, 2020)
Erysipelas, caused by the bacterium Erysipelothrix rhusiopathiae, is re-emerging in swine and poultry production systems worldwide. While the global genomic diversity of this species has been characterized, how much of this genomic and functional diversity is maintained at smaller scales is unclear. Specifically, while several key immunogenic surface proteins have been identified for E. rhusiopathiae, little is known about their presence among field strains and their divergence from vaccines, which could result in vaccine failure. Here, a comparative genomics approach was taken to determine the diversity of E. rhusiopathiae strains in pigs in Great Britain over nearly three decades, as well as to assess the field strains’ divergence from the vaccine strain most commonly used in British pigs. In addition, the presence/absence and variability of 13 previously described immunogenic surface proteins was determined, including SpaA which is considered a key immunogen. We found a high diversity of E. rhusiopathiae strains in British pigs, similar to the situation described in European poultry but in contrast to swine production systems in Asia. Of the four clades of E. rhusiopathiae found globally, three were represented among British pig isolates, with Clade 2 being the most common. All British pig isolates had one amino acid difference in the immunoprotective domain of the SpaA protein compared to the vaccine strain. However, we were able to confirm using in silico structural protein analyses that this difference is unlikely to compromise vaccine protection. Of 12 other known immunogenic surface proteins of E. rhusiopathiae examined, 11 were found to be present in all British pig isolates and the vaccine strain, but with highly variable degrees of conservation at the amino acid sequence level, ranging from 0.3 to 27% variant positions. Moreover, the phylogenetic incongruence of these proteins suggests that horizontal transfer of genes encoding for antigens is commonplace for this bacterium. We hypothesize that the sequence variants in these proteins could be responsible for differences in the efficacy of the immune response. Our results provide the necessary basis for testing this hypothesis through in vitro and in vivo studies.